Geometry Math Problem-Solving Ability in Grade IV Elementary School Students Based on Learning Style - Lestari, Mutiara Intan; Wijayaningputri, Arinta Rezty; Anshory, Ichsan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
According to Miles and Huberman, this research uses a descriptive qualitative method with three steps of data analysis: data reduction, data presentation, and conclusion drawing. Data collection techniques included observation, interviews, and documentation. The study aimed to analyze the relationship between students' learning styles and how they solve geometry math problems. Initial observations in class IV SDN Pulorejo III showed that students' literacy skills were low, especially in understanding story problems, obstacles in solving geometry problems such as memorizing formulas, and ignorance of students' learning styles. The results revealed that 54% of students have a visual learning style, 18% auditory, and 28% kinesthetic. Different learning styles affect how students acquire and process information and their problem-solving strategies. Therefore, a varied learning approach must accommodate all students' learning styles. This research emphasizes the importance of applying learning methods that suit students' learning styles to improve their understanding of mathematics concepts and critical thinking skills. Thus, each student can learn more effectively according to how they understand information.